Detecting Iron Deficiency Anemia in Type C Hospital: Role of RDW and MCV Parameters - Marina Ludong; Ninik Sukartini; Nuri Dyah Indrasari; Dewi Wulandari (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
Iron deficiency anemia remains a global health problem, which is also a prominent cause of morbidity and mortality of all range of ages. There are three stages of anemia development, and there are some parameters to detect bodily iron status. Transferrin saturation is one of the reliable parameters. Among all hematology parameters, Red Cell Distribution Width (RDW) and Mean Corpuscular Volume (MCV) are two of the most often studied. MCV and RDW are relatively affordable and accessible, most importantly for rural areas with lower socioeconomic status. This was an analytical observational study with a cross-sectional design aimed to determine the correlation between RDW and MCV values with iron deficiency anemia, which was measured by transferrin saturation. A significant correlation was found between RDW, MCV values, and iron deficiency anemia in patients of Mitra Keluarga Cikarang Hospital and Permata Keluarga Hospital, Jakarta with a p-value of <0.05. Sensitivity and specificity for MCV were 75% and 100%, for RDW were 55.45% and 80%, respectively. In conclusion, RDW and MCV parameters can be used as screening instruments for iron deficiency anemia.